Pengaruh Faktor Internal Perusahaan terhadap Kebijakan Dividen Pada Perusahaan LQ45 - Mita Handayani; Anita Wijayanti; Suhendro Suhendro (Universitas Batanghari Jambi, 2021)
Expecting income or return from the company is the general target of investors in investing. Dividends are one of the incomes that investors want. This study aims to analyze the influence of profitability, liquidity, company size, sales growth and IOS on dividend policy. For this research was taken in LQ45 companies listed on the Indonesia Stock Exchange for the period 2015 to 2019. Through purposive sampling selected 18 companies that meet the research criteria, so that the sample is 90 observations. Data testing method through multiple linear regression. The results of the study based on the F test showed that all independent variables in the study had a simultaneous effect on dividend payout ratio, while based on t-test resulting in profitability, company size and IOS had no effect on dividend payout ratio, but liquidity had an effect on dividend payout ratio and sales growth negatively affected dividend payout ratio.